2021
DOI: 10.1111/tri.13987
|View full text |Cite
|
Sign up to set email alerts
|

Graft utilization after normothermic regional perfusion in controlled donation after circulatory death—a single‐center perspective from France

Abstract: Normothermic regional perfusion (NRP) in controlled donation after circulatory death (cDCD) is a promising procurement strategy. However, a detailed analysis of graft utilization rates is lacking. This retrospective study included all cDCD donors proposed to a single center for NRP procurement of at least one abdominal organ from 2015 to 2020. Utilization rates were defined as the proportion of transplanted grafts from proposed donors in which withdrawal of life sustaining therapies (WLST) was initiated. In to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 34 publications
(60 reference statements)
0
23
0
Order By: Relevance
“…Of the 14 studies published between 2003 and 2021, 12 studies (86%) were published after 2014 (Table 1). [10][11][12][13][14][15][16][17][18][19][20][21][22][23] All study designs were retrospective cohort studies. No randomized clinical trials were found.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 14 studies published between 2003 and 2021, 12 studies (86%) were published after 2014 (Table 1). [10][11][12][13][14][15][16][17][18][19][20][21][22][23] All study designs were retrospective cohort studies. No randomized clinical trials were found.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…[11] Donor age limitation varied from 65 years up to no limit. [10][11][12][13][14][15][16][17] Compared with uDCD protocols, restrictions…”
Section: Current Criteria For Consideration Of Anrp In Cdcdmentioning
confidence: 99%
See 2 more Smart Citations
“…In published protocols, 44,45,47–52 they are measured immediately before starting NRP, after 1 h, and at the end of reconditioning. More frequent measurements are also reported 19–53 . Barcelona's team 44,45 adopted a threshold based on a maximum of three times the upper limit of normality at baseline and of four times at the end of NRP.…”
Section: Methodsmentioning
confidence: 99%